Effect of Income Level, Taxation Sanctions And The Tax Rates on It Individual Taxpayer Compliance At KPP Pratama Jakarta Kebayoran Lama: EFFECT OF INCOME LEVEL, TAXATION SANCTIONS AND THE TAX RATES ON IT INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA JAKARTA KEBAYORAN LAMA - Ahmadi, Wahyu; Purwatiningsih, Purwatiningsih (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research aims to determine the influence of income levels, tax sanctions and tax rates on personal taxpayer compliance at KPP Pratama Kebayoran Lama. The type of research used in this research is quantitative research. The population in this study were individual taxpayers of the KPP Pratama Kebayoran Lama. The sample for this research was determined using the Slovin formula so that the total sample was 100 samples. The data analysis technique used is Multiple Linear Regression with the SPSS version 25 program. The research results show that simultaneously the level of income, tax sanctions and tax rates influence taxpayer compliance. Income level influences taxpayer compliance. Tax sanctions affect taxpayer compliance. Tax rates influence taxpayer compliance. System have a positive effect on motor vehicle taxpayer compliance.